Radio Frequency Identification (RFID)-Based Validated Electronic Lock for Automatic Monitoring System - Saputra, S D; Alam, Syaiful; Purwiyanti, Sri; Nasrullah, Emir; Sadnowo, Ageng (Journal of Applied Science, Engineering and Technology, 2021)
This study aims to create a prototype of an electronic key system using internet of things-based RFID with a validated monitoring system with registered data. This system is applied to the door of the Integrated Laboratory of the Department of Electrical Engineering, University of Lampung. The electronic keys that are created are very difficult to break into and also easy to change the access secret code to maintain confidentiality. The developed electronic door lock device has strong security reliability with code validation. The code validation block serves as a door unlock determinant. The validated data will produce a signal 1 which will drive the actuator, in this case the door lock solenoid, to work (lock open). The security code has 2554 combinations. To access the door from outside, the RFID tag should be registered in the database and permitted by administration and the ID number data is on the processor. The counter will count the number of people who pass through the door, if more than one person then the buzzer will sound. Then the door lock solenoid is closed and will lock the door again. From the experimental results it is found that this system can work well with a minimum delay of 1.8 s obtained at a distance between devices of 5 m.